Faktor yang Berhubungan dengan Penyediaan Dokumen Rekam Medis Rawat Jalan di RSUP H. Adam Malik Medan - Berliana Berliana; Mappeaty Nyorong; Nuraini Nuraini (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
According to Permenkes 269/2008 concerning medical records in Article paragraph 1, medical records are files containing notes and documents about patient identity, examination, treatment, action, and other services that have been provided to patients. Several things that can support the distribution of outpatient medical record files can be carried out properly are the ability of medical record officers, medical record management systems and adequate storage locations. The purpose of this study was to determine the factors related to the time of providing outpatient medical record files at RSUP H. Adam Malik Medan.The study used an analytic survey method with a cross sectional approach. The population of this study was outpatient medical record officers in as many as 75 officers with a sample using a total sample technique of 75 officers. Data analysis used univariate analysis and bivariate analysis with chi-square test statistics.The results of the chi-square test analysis showed that the p-value of each variable, including knowledge, obtained p-value = 0.026, human resources obtained p-value = 0.013 and infrastructure obtained p-value = 0.005.The conclusion of this study is that there is an influence of knowledge, human resources and infrastructure with the time of providing outpatient medical record files. It is hoped that it can increase the knowledge of medical record officers in hospitals through the provision of medical record training as well as improve the function of the quality committee in hospitals related to the implementation and provision of medical record documents, increase the number of human resources in the field of medical records in each unit and improve monitoring and evaluation functions for staff officers who do not work according to the standard of providing medical records, increasing the number of file storage racks, and providing the use of different lifts so that the distribution of RM documents is carried out faster